SURVEI IDENTIFIKASI KONDISI KERUSAKAN BIJI KOPI LIBERIKA TUNGKAL KOMPOSIT DAN PENYEBABNYA DI SIMPANAN - Susi Rahayu; Hayata Hayata; Araz Meilin (Universitas Batanghari, 2022)
Damage to coffee beans which is stored in storehouse due to insect pests can reduce its quality through a decrease in coffee weight and its quality, consequently causing the price of coffee beans decrease because they have low quality. The purpose of the study was to identify the damaged condition of the Libtukom coffee and to find out the cause of the damage to the stored coffee been. This research was carried out in Mekar Jaya Village, Betara District, West Tanjung Jabung Regency, Batanghari University Laboratory and BPTP Pest Laboratory Jambi since August to October 2021. This research was carried out at 4 locations where farmers' coffee beans storehouse using the light and bait trap method. and handpicking. This research was conducted by taking samples of coffee beans that were attacked by insect pests as much as 4 kg each sample so that 16 kg was obtained. The observed parameters were the characteristics of coffee damage, the number of insects caught, characteristics of the storehouse of Libtukom coffee beans and the moisture content of the stored coffee beans. The data were analyzed descriptively using the mean/mean value, standard deviation and presented in tabular form. The results showed that the highest characteristics of the damage to coffee beans in the four storage locations were the hollo seed more than one hole, followed by spoted bean and then one hole in hollo bean. The amount obtained on the insect catching method in the warehouse of Libtukom coffee bean using bait traps was Araecerus fasciculatus that obtained more, while light traps showed more the other insect.